2020
DOI: 10.34133/2020/2038560
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable, Elastic, and Sensitive MXene-Based Hydrogel for Flexible Strain and Pressure Sensors

Abstract: Electronic skin is driving the next generation of cutting-edge wearable electronic products due to its good wearability and high accuracy of information acquisition. However, it remains a challenge to fulfill the requirements on detecting full-range human activities with existing flexible strain sensors. Herein, highly stretchable, sensitive, and multifunctional flexible strain sensors based on MXene- (Ti3C2Tx-) composited poly(vinyl alcohol)/polyvinyl pyrrolidone double-network hydrogels were prepared. The un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 50 publications
2
86
1
Order By: Relevance
“…MXene, with its highly conductive properties, was previously implemented in the development of conductive hydrogels such as an MXene-catalyzed poly­(acrylic acid) (PAA) hydrogel, a MXene-hyaluronic acid/alginate hydrogel, and MXene-composited poly­(vinyl alcohol)/poly­(vinyl pyrrolidone) double-network hydrogels. ,, In our study, MXene enhanced the conductivity of low-concentration GelMA to 0.65 ± 0.04 and 0.94 ± 0.12 S/m when 0.05 and 0.1 mg/mL concentrations were used, respectively. Conductivity values achieved by either the addition of AuNPs or MXene were in the range of electrical conductivity of the excitable tissues (0.4–0.9 S/m), which indicates that such hydrogels are biomimetic and of physiological relevance.…”
Section: Results and Discussionmentioning
confidence: 68%
“…MXene, with its highly conductive properties, was previously implemented in the development of conductive hydrogels such as an MXene-catalyzed poly­(acrylic acid) (PAA) hydrogel, a MXene-hyaluronic acid/alginate hydrogel, and MXene-composited poly­(vinyl alcohol)/poly­(vinyl pyrrolidone) double-network hydrogels. ,, In our study, MXene enhanced the conductivity of low-concentration GelMA to 0.65 ± 0.04 and 0.94 ± 0.12 S/m when 0.05 and 0.1 mg/mL concentrations were used, respectively. Conductivity values achieved by either the addition of AuNPs or MXene were in the range of electrical conductivity of the excitable tissues (0.4–0.9 S/m), which indicates that such hydrogels are biomimetic and of physiological relevance.…”
Section: Results and Discussionmentioning
confidence: 68%
“…The hydrogel, with a unique three-dimensional (3D) hydrophilic polymer network, performs high stretchability, exceptional biocompatibility, and degradability, exert broad application prospects in the fields of biological wound dressings, drug delivery, sensors, actuators, and flexible energy storage devices [22][23][24][25][26][27]. Ionic liquids are a group of organic salts comprised of organic cations and organic or inorganic anions [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…They have wide-range applications for monitoring surface strains of human skin due to joint motion, tissue swelling, wound healing, or even emotional expression. [5][6][7] Different types of flexible strain sensors have been reported. [8][9][10][11] However, practical implementation of these strain sensors for skinmountable and wearable applications still remains a great challenge due to the sophisticated measurement equipment, poor resolution, and/or poor dynamic performance of the senosrs.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] For example, Liu Q. et al reported a graphenebased device with a fish-scale microstructure configuration, and achieved a sensing range up to 82% strain, a GF value of 16.2−150 and excellent reliability and stability (>5000 cycles). 24 Lin, L. et al proposed a facile preparation method for superhydrophobic and multi-functional conductive nanofiber composites (CNCs) with a dual conductive network, and the CNCs based strain sensor possesses an extremely large GF value of 1.04×10 5 , with the strain range from 20% to 70%. 25 Li, Q. et al developed strain sensors using ultraviolet/ozone (UV/O3) treated CNT/Ecoflex, and achieved a high sensitivity up to 1020.2 and a stretchability up to 100%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation